The Influence of Principal’s Managerial Skills and Work Motivation on Teacher Performance at Junior High Schools in Tompaso and West Tompaso Districts - Laurina Jafar; Deitje Adolfien Katuuk; Romi Junior Mongdong (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze: (1) the partial influence of the principal's managerial skills on teacher performance; (2) the partial influence of work motivation on teacher performance; and (3) the simultaneous influence of both the principal's managerial skills and work motivation on teacher performance at Junior High Schools (SMP) in Tompaso and West Tompaso Districts. The background of this research is the stagnation of teacher performance, characterized by the continued use of conventional teaching methods and fluctuating levels of motivation in managing complex curricular administrations. The research employed a quantitative approach with a survey method. The population consisted of 71 junior high school teachers in Tompaso and West Tompaso Districts, where the samples are 42 people. Data were collected through questionnaires and analyzed using Multiple Linear Regression techniques via SPSS 29 software. The results of the study indicate that: (1) The principal's managerial skills have a positive and significant influence on teacher performance, with a regression coefficient of 0.380; (2) Work motivation has a positive and significant influence on teacher performance, with a regression coefficient of 0.618. Work motivation was found to be the most dominant variable influencing teacher performance in the region; (3) Simultaneously, the principal's managerial skills and work motivation significantly influence teacher performance with an F-value of 54.420 (p < 0.001). The combined contribution of these two variables to the variation in teacher performance (R-Square) is 73.6%, while the remaining 26.4% is influenced by other factors outside this research model.